Interior of the Church of St. Cassius and St. Florentius, Bonn - Asselineau, Léon Auguste, 1808-1889 (lithographer):::Creator::::::::::::; Latteux, Eugène, 1805-1850 (artist):::Contributor:::::::::::: (Paris; A. Hauser, 2020)
Lithograph of the interior of the Münster (also called the church of St. Cassius and St. Florentius) in Bonn